EFL Students’ Strategies in Reading Printed and Digital Texts - Luthfiyatun Thoyyibah; Iskhak Said; Hilmiatul Asna (Universitas Galuh, 2026)
Reading strategies are crucial for EFL students to comprehend texts, both in print and digital formats. The rapid development of digital media has influenced students' reading habits and skills. Previous research has primarily focused on reading preferences and comprehension between print and digital texts, but few have highlighted the strategies students use and the challenges they face across both media. This study aims to explore the strategies employed by first-year EFL students in reading print and digital texts, as well as the difficulties they encounter. This study employed a qualitative approach with a case study design. First-year students from the English Language Education Study Program at Galuh University participated. Data were collected through classroom observations and semi-structured interviews, then analyzed using thematic and content analysis. Students used strategies such as skimming, scanning, highlighting, note-taking, and rereading across both printed and digital texts, though their application varied depending on the medium. For digital texts, additional strategies such as screen adjustment and the use of online translation tools were also identified. Challenges include notification distractions, eye fatigue when reading digitally, and difficulty finding information quickly in print texts. These findings highlight the importance of adaptive reading strategies for improving students' digital comprehension and literacy and provide input for educators to develop more effective teaching practices.